Housing adaptations and housing accessibility problems among older adults with long-standing spinal cord injury. (December 2021) - Norin, Lizette; Slaug, Björn; Haak, Maria; Iwarsson, Susanne
Introduction: Adults with spinal cord injuries are living longer than previously, and a majority are living in ordinary housing in the community. Housing accessibility is important for maintaining independent occupational performance for this population, but knowledge in this area is insufficient. We investigated housing adaptations and current accessibility problems among older adults with long-standing (>10 years) spinal cord injuries. Method: Data from home visits among 122 older adults with spinal cord injuries in Sweden were used. Housing adaptations and environmental barriers were descriptively analysed. Findings: Kitchens, entrances, and hygiene areas were common locations for housing adaptations and environmental barriers that generated accessibility problems. The most common adaptations were ramps, wheelchair-accessible stovetops, and ceiling-lifts. Wall-mounted cupboards and high shelves (kitchen), inaccessible storage areas (outside the dwelling), and a lack of grab bars (hygiene area) generated the most accessibility problems. Conclusion: Despite housing adaptations, there are considerable accessibility problems in the dwellings of older adults with long-standing spinal cord injuries in Sweden, indicating that long-term follow-up of the housing situation of this population is necessary. Focusing on accessible housing as a prerequisite for occupational performance is at the core of occupational therapy, deserving attention on the individual as well as the societal level.